Improving Learning Outcomes in the Fiqh Subject, Friday Prayer Chapter, Using the Demonstration Method for Grade 7 Students at MTs Darun Nahwi Singajaya Indramayu - Muhammad Chaidir (Manajia: Journal of Education and Management, 2025)
The writing of this journal is motivated by the existence of students who do not understand the material on the chapter of Friday prayers, both from the obligatory, pillars, procedures, implementation and so on related to Friday prayers. In other words, the lack of interest in learning students, especially class 7 MTs Darun Nahwi towards the material on Friday prayers in the Fiqh subject. So that this has an impact on the low learning achievement of students at MTs Darun Nahwi in class 7, so it is necessary to increase the interest of students in learning the fiqh subject on the chapter of Friday prayers. So that students can know and understand the material on the fiqh subject on the chapter of Friday prayers. I use the demonstration method when teaching. Because, basically they tend to like the demonstration method more than the lecture method. Therefore, this study aims to expand knowledge and improve the learning outcomes of students at MTs Darun Nahwi. As the author, I took the title of this journal.